Metastatic Organotropism Differential Treatment Response in Urothelial Carcinoma: A Systematic Review and Network Meta-analysis of Randomized Controlled Trials - Kardoust Parizi, Mehdi; Matsukawa, Akihiro; Bekku, Kensuke; Klemm, Jakob; Alimohammadi, Arman; Laukhtina, Ekaterina; Karakiewicz, Pierre; Chiujdea, Sever; Abufaraj, Mohammad; Krauter, Johanna; Shariat, Shahrokh F (European urology oncology, 2024)
CONTEXT: The optimal therapeutic agent with respect to metastatic sites is unclear in advanced urothelial carcinoma (UC). OBJECTIVE: To investigate the metastatic organotropism differential treatment response in patients with advanced or metastatic UC. EVIDENCE ACQUISITION: A systematic search and network meta-analysis (NMA) was performed according to the Preferred Reporting Items for Systematic Reviews and Meta-analyses statement. The primary endpoints of interest were the objective response rate, overall survival (OS), and progression-free survival with respect to different metastatic sites. EVIDENCE SYNTHESIS: Twenty-six trials comprising 9082 patients met our eligibility criteria, and a formal NMA was conducted. Durvalumab plus tremelimumab as first-line systemic therapy was significantly associated with better OS than chemotherapy in visceral metastasis (hazard ratio [HR] 0.81, 95% confidence interval [CI] 0.67-0.98). Pembrolizumab as second-line systemic therapy was significantly associated with better OS than chemotherapy in patients with visceral metastasis (HR 0.75, 95% CI 0.60-0.95). Atezolizumab as second-line systemic therapy was significantly associated with better OS than chemotherapy in patients with liver metastasis (in the population of >5% of tumor-infiltrating immune cells) and lymph node metastasis (HR 0.51, 95% CI 0.28-0.96, and HR 0.59, 95% CI 0.37-0.96, respectively). CONCLUSIONS: Administration of immune-oncology treatments with respect to metastatic sites in patients with advanced or metastatic UC might have a positive impact on survival outcomes in both the first- and the second-line setting. Nevertheless, further investigations focusing on metastatic organotropism differential response with reliable oncological outcomes are needed to identify the optimal management strategy for these patients. PATIENT SUMMARY: Although the supporting evidence for oncological benefits of therapeutic systemic agents with respect to metastatic sites is not yet strong enough to provide a recommendation in advanced or metastatic urothelial carcinoma, clinicians may take into account tumor organotropism only in discussion with the patient fully informed on the optimal treatment decision to be taken.
Keywords: urologické nádory; Urologic Neoplasms; Bladder cancer; Chemotherapy; Neoplasm Metastasis; metastázy nádorů; karcinom z přechodných buněk; výsledek terapie; Humans; Metastatic urothelial carcinoma; Organotropism; lidé; Randomized Controlled Trials as Topic; Immunotherapy; Treatment Outcome; Carcinoma, Transitional Cell; randomizované kontrolované studie jako téma